Kinetics and effect of temperature in anaerobic fluidised bed reactors with clayey supports - Duran-Barrantes, M. M. (Array, 2008)
Summary: An anaerobic treatment in batch regime of swine wastewater was carried out. Five stirred tank reactors were used, one of them containing suspended biomass for reference, and the other four with various suspended micronised clay supports of different chemical composition (saponite, zeolite, calcined sepiolite and esmectite). The experimental device was maintained at three different temperatures: 25, 35 and 47 °C. The obtained removal efficiency ( COD/%) was about 80 % at 25 °C, in reactors containing esmectite, saponite and calcined sepiolite support. The reactor with zeolite support showed the minimum mean concentrations in NH4 +–N and volatile acids in the effluents, at any temperature. The Romero methane production kinetic model has been applied obtaining the value of the maximum specific growth rate of microorganisms, max, and the specific kinetic constant, k, for each temperature studied. The highest mean max was obtained at 25 °C and a decrease was observed as the temperature applied increased